2022
DOI: 10.1021/acsami.2c03589
|View full text |Cite
|
Sign up to set email alerts
|

Precise Controlling of Friction and Adhesion on Reprogrammable Shape Memory Micropillars

Abstract: Microstructured surfaces with stimuli-responsive performances have aroused great attention in recent years, but it still remains a significant challenge to endow surfaces with precisely controlled morphological changes in microstructures, so as to get the precise control of regional properties (e.g., friction, adhesion). Herein, a kind of carbonyl iron particle-doped shape memory polyurethane micropillar with precisely controllable morphological changes is realized, upon remote near-infrared light (NIR) irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Introducing photothermal conversion materials into thermally responsive SMPs is a feasible approach for light-stimulated surface tuning. Shao et al [91] developed a novel shape-memory reprogrammable micropillar based on a composite of shape memory PU and carbonyl iron particles (CIPs) with a diameter of 2-8 µm, where the diameter, height, and distance between the micropillars at the bottom of the micropillars were 60-120 µm. When the compressed shape memory reprogrammable micropillar surface was exposed to near-infrared (NIR) light with a power of 0.5 W, the temperature of the local area sharply increased above 50 °C within 2 s, remotely triggering the structure recovery of targeted area immediately.…”
Section: Light Stimulusmentioning
confidence: 99%
“…Introducing photothermal conversion materials into thermally responsive SMPs is a feasible approach for light-stimulated surface tuning. Shao et al [91] developed a novel shape-memory reprogrammable micropillar based on a composite of shape memory PU and carbonyl iron particles (CIPs) with a diameter of 2-8 µm, where the diameter, height, and distance between the micropillars at the bottom of the micropillars were 60-120 µm. When the compressed shape memory reprogrammable micropillar surface was exposed to near-infrared (NIR) light with a power of 0.5 W, the temperature of the local area sharply increased above 50 °C within 2 s, remotely triggering the structure recovery of targeted area immediately.…”
Section: Light Stimulusmentioning
confidence: 99%
“…To better trigger the mechanical deformations of the artificial micropillars, various types of micropillars that can respond to different external stimuli have been designed and fabricated. According to the actuation source, the micropillars can be mainly classified as thermo-driven, [24][25][26] pH-driven, [22,27,28] light-driven, [29][30][31] magnet-driven, [32][33][34] electricity-driven, [35][36][37] and ultrasound-driven. [38,39] The micropillars composed of pHsensitive hydrogels can swell or shrink at different pH while the toxic fuels would compromise their biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Recently, intelligent surfaces with switchable isotropic/anisotropic droplet rolling states have been extensively reported, which are expected to overcome the limitation rooted in pre-vious fixed surfaces. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] For example, Wang et al reported a switchable surface with vertically and temporarily inclined microarrays using a shape memory polymer (SMP) for droplet transport and information storage; 22 Li et al prepared a SMPbased microcone array doped with iron powder particles for multifunctional droplet manipulation and could readily switch between vertical and curved states. 26 Despite the advances in switching between isotropic and anisotropic rolling states using these strategies, dynamic liquid droplet control with fast response and no loss still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…26 Despite the advances in switching between isotropic and anisotropic rolling states using these strategies, dynamic liquid droplet control with fast response and no loss still remains a challenge. Most of the reported switchable surfaces require specific SMP materials to shift the surface morphology via their intrinsic shape memory property, such as polyurethane, [16][17][18][19][20] epoxy resin, [21][22][23][24][25][26][27][28][29][30] azobenzene polymers, 31 etc., which are usually assisted by heating-applying external force-cooling [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] or light radiation 31 and are unable to rapidly switch the surface state in real time. As a result, the materials preparation and regulation are rather complicated and high-cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation